Calcaneonavicular coalition resection with fat graft - Javier Masquijo, MD; Vincent S. Mosca, MD (Elsevier, 2024)
ABSTRACT: Calcaneonavicular coalitions can cause foot and ankle pain, as well as loss of function. Surgical excision and graft interposition are the standard of care for patients with calcaneonavicular coalitions and recurrent and disabling symptoms. The purpose of this manuscript and the accompanying video is to provide a detailed step-by-step description of a Calcaneonavicular coalitions treated by resection and interposition of an autologous fat graft. Key Concepts: (1) A preoperative MRI or CT scan is essential to rule out associated coalitions on the same foot and to assess foot alignment. (2) Fluoroscopy and correct orientation of osteotomes are essential to ensure complete resection without inadvertently removing too much of the navicular or damaging the cuboid or talar head. (3) It is important to resect plantar periosteum and place autologous fat from the proximal medial thigh region to avoid reossification.